Symbiotes of the Digital Environment: to the Epidemiological Theory of the Interface - K. А. Ocheretyany (Дискурс, 2022)
Introduction. In modern life sciences, it is impossible to ignore the problems of viruses, bacteria, parasites and their impact on the ecosystems. But the interface is a human ecosystem of the digital age and a new formation of life, which means that it also needs to be understood from subdiscursive elements, such as digital analogues of viruses, bacteria, and parasites.Methodology and sources. Methodologically, the work is based on a philosophical analysis of the challenges and precedents of the digital field, examples of research literature, the methods of media philosophy, anarchist epistemology, and philosophical epidemiology are applied (M. Foucault, K. Kukso).Results and discussion. The article shows that the epistemological understanding of the interface should be supplemented with an epidemiological understanding, otherwise the principles and forms of life translated into numbers will elude theory.The interface is thought of as a condition of possibilities: discursive, instrumental, demonstrative. The interface is seen as an epistemological configuration (from the Greek ῐ̔ѧστημῐ, i.e. not just “possessing knowledge”, but “possessing”, – to establish, appoint) – as a form of power, i.e. as a series of forced measures, reacting to something not completely determined, spontaneous, but imperceptibly limiting and transforming the will, the very logic of the act, or the pragmatics of the action.Conclusion. To understand the interface, it is necessary to shift attention from various plugins, drivers, interactive mechanics that determine epistemological possibilities to microprocesses that build the interface as a user experience based on epidemiological restrictions.